The Effect Of Protean Career Orientation On Teachers’ Intention To Quit With Mediation Of Perceived Marketability In Karachi - Khan, Hira (2020)
This study highlights the emergence of a new concept of career, which is hardly introduced in the Pakistani context and also briefs about the educational conditions of the private primary education sector of Karachi. This district has the highest enrolment in private primary schools in comparison to other 22 districts of Sindh province, Pakistan. The purpose for studying intention to quit amongst teachers is an unforeseen upsurge in actual turnover behaviour among teachers of this sector, and several authors are certain upon a fact that intention is an instant antecedent of actual behaviour. Since it is difficult to investigate from the teachers once they leave the organization, so intention to quit seems quite supportive in scrutinizing the actual problem of teachers’ turnover behaviour. The changing orientations of career mindsets among teachers are one of the reasons for being dependent on their choices (as per their work values) and they tend to be more self-directed by now. Education, an essential part of anyone’s life is in the hands of teachers. In the educational sector of Pakistan, the education is the most serious concern due to huge population especially in primary sector. This study focused on 274 private primary teachers of Karachi as the sample to investigate the effects of protean career orientation (an independent career mindset) on the their intention to quit via mediating effects of the perception about their internal and external marketability.